2013
DOI: 10.1108/pr-10-2011-0146
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive examination on antecedents of cultural intelligence: case of South Korea

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 57 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…Both the depth and breadth of exposure showed positive relationships with CQ (Crowne, 2013). The previous working experience of expatriates (1) in the overseas department of their employer and (2) with foreign nationals within their home country prior to their expatriation displayed a positive relationship with cognitive CQ and metacognitive CQ, respectively (Moon, Choi & Jung, 2013). The number of local staff http://www.sajhrm.co.za Open Access members in the host country with whom expatriates worked presented a positive relationship with all of the CQ dimensions .…”
Section: Theme 4: International Experience and Exposure Progress Cultmentioning
confidence: 75%
“…Both the depth and breadth of exposure showed positive relationships with CQ (Crowne, 2013). The previous working experience of expatriates (1) in the overseas department of their employer and (2) with foreign nationals within their home country prior to their expatriation displayed a positive relationship with cognitive CQ and metacognitive CQ, respectively (Moon, Choi & Jung, 2013). The number of local staff http://www.sajhrm.co.za Open Access members in the host country with whom expatriates worked presented a positive relationship with all of the CQ dimensions .…”
Section: Theme 4: International Experience and Exposure Progress Cultmentioning
confidence: 75%
“…The antecedents of CQ can be individual or situational in nature. Previous studies have shown that factors such as prior international experience, personality traits and skills, formal training programs or experiential learning programs are possible antecedents of CQ [10,[23][24][25][26]. In this context, HEIs play an important role in promoting levels of CQ, especially in preparing students for the labor market.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified a range of individual difference factors associated with higher CQ, some of which relate to cognitive abilities and styles. For example, language ability (Li, Mobley, & Kelly, 2013), selfmonitoring (Koo Moon, Choi, & Jung, 2013), cognitive flexibility (Bernardo & Presbitero, 2018), context dependence (Adair, Buchan, Chen, & Liu, 2016), and social intelligence (Depaula, Azzollini, Cosentino, & Castillo, 2016) have all been shown to be positively associated with overall CQ scores. Personality, measured primarily using the Big Five personality dimensions, has been the focus of several studies of CQ.…”
Section: Introductionmentioning
confidence: 99%